Cytoplasmic and nuclear morphometric parameters in cytologic preparations of canine cutaneous mast cell tumors - Torres Neto, Rafael; Pinczowski, Pedro; Rahal, Sheila C.; Kitchell, Barbara E.; Amorim, Renée L. (Brazilian Journal of Veterinary Pathology, 2010)
Thirty fine-needle biopsy (FNB) samples from 28 dogs subjected to surgical resection of cutaneous mast cell tumors (MCTs) were stained with Giemsa. At least 100 neoplastic cells from each cytology slide were evaluated by morphometric analysis. The parameters were: area, perimeter of the cell, cytoplasm, nucleus and circumference factor. MCTs of grade III had a mean cellular area of 231.70 μm2 ± 57.1, and grade II had a mean of 252.30 μm2 ± 55.0. Cellular perimeter was 61.20 ± 7.1 in grade II and 59.1 ± 8.6 in grade III. Cellular parameters were not statistically different between grades (p> .05). Mean nuclear area was 88.90 μm2 ± 19 in grade III and 72.30 μm2 ± 13.9 in grade II, with statistical difference between grades (P = .011). Mean nuclear perimeter was 32.40 μm ± 3.0 in grade II and 35.70 μm ± 4.0 in grade III, with statistical difference between grades (P = .018). Mean nuclear circumference factor was 1.0 ± 0.33 in grade II and 1.1 ± 0.28 in grade III, with no statistical difference between grades (P = 0.78). Nuclear-tocytoplasmic ratio in grade II was 0.29 ± .07 and 0.39 ± .08 in grade III, with statistical difference (P = .02). The number of binucleated and multinucleated cells and mitotic figures was significantly increased in grade III MCTs (P < .001). In conclusion, the number of mitotic figures, presence of binucleation and multinucleation, and nuclear-to-cytoplasmic ratio can help to guide a profile of MCT aggressiveness in cytologic preparations.